Determination of Benzylpenicillin Potassium Residues in Duck Meat Using Surface Enhanced Raman Spectroscopy with Au Nanoparticles - Yijie Peng; Muhua Liu; Jinhui Zhao; Haichao Yuan; Yao Li; Jinjiang Tao; Hongqing Guo (Journal of Spectroscopy)
A new method using surface enhanced Raman spectroscopy (SERS) with Au nanoparticles was established for the rapid detection of benzylpenicillin potassium (PG) residues in duck meat. Au nanoparticles were used as SERS enhancement substrate, and the maximum absorption peak of Au nanoparticles using the UV-Vis spectrophotometer was 548 nm. In the research, the SERS spectra of PG solutions and PG duck meat extract as well as their vibrational assignment were analyzed. The effects of Au nanoparticles addition, sample addition, NaCl solution addition, and adsorption time on the SERS intensities of PG duck meat extract were discussed. It is revealed that a good linearity can be obtained between the SERS intensities at 993 cm−1 and the PG residues concentrations (0.5~15.0 mg·L−1) detected in duck meat extract. The linear equation was Y=831.68X+1997.1, and the determination coefficient was 0.9553. The determination coefficient of PG in duck meat extract between the actual values and the predictive values was 0.9757, and the root mean square error (RMSEP) was 0.6496 mg/L. The recovery rate of PG in duck meat extract was 90~121%. The results showed that the method using SERS with Au nanoparticles could pave a new way for the rapid detection of PG residues in duck meat.